Review of genus Hydropsyche Pictet 1834 (Insecta: Trichoptera: Hydropsychidae) from India - Pandher, Manpreet S.; Kaur, Simarjit; Parey, Sajad H.; Saini, Malkiat S. (Zootaxa, 2017)
The genus Hydropsyche is reviewed from India. Three new species are described and illustrated belonging to genus Hydropsyche. The newly described species are Hydropsyche curvata sp. nov., H. hajinensis sp. nov., both from Jammu & Kashmir, and H. golitarensis sp. nov. from Sikkim. Hydropsyche quadrata Malicky & Chantaramongkol 2000 (from Sikkim), H. augeias Malicky & Chantaramongkol 2000 (from Uttarakhand) and H. camillus Malicky & Chantaramongkol 2000 (from Sikkim and Himachal Pradesh) are reported for the first time from India. Hydropsyche athamas Malicky & Chantaramongkol 2000, H. homunculus Schmid 1965, and H. harpagofalcata Mey 1995 are also redescribed and reported for the first time from India. Hydropsyche nuristanica Schmid 1963 (from Jammu and Kashmir) and H. rakshakaha Oláh 1994 (from Jammu and Kashmir, Himachal Pradesh, Uttarakhand, and West Bengal) are reported from these states for the first time. Hydropsyche charon Malicky & Chantaramongkol 2000, from Uttarakhand, H. appendicularis Martynov 1931, and H. pallipenne Banks 1938 are also redescribed and reported from Himachal Pradesh. Hydropsyche claviformis Mey 1996 is also redescribed based on a specimen from Sikkim. Furthermore, the male is redescribed and a neotype is designated for Hydropsyche asiatica Ulmer 1905. Hydropsyche chotanagpurensis is a nomen novum, replacing junior homonym Hydropsyche ulmeri (Martynov 1935). With these additions, the total number of Indian species for genus Hydropsyche is now 54. A catalogue of known Indian species is also given.